Testing the adaptive advantage of a threatened species over an invasive species using a stochastic population model. (15th June 2020) - Brown, Timothy R.; Todd, Charles R.; Hale, Robin; Swearer, Stephen E.; Coleman, Rhys A.
Abstract: Introduced species are a major threat to freshwater biodiversity. Often eradication is not feasible, and management must focus on reducing impacts on native wildlife. This requires an understanding of how native species are affected but also how environmental characteristics influence population dynamics of both invasive and native species. Such insights can inform how to manipulate systems in order to take advantage of life-history traits native species possesses that invaders do not. The highly invasive fish, Gambusia holbrooki, has been implicated in the decline of many freshwater fish and amphibians. In south-eastern Australia, one of these is the threatened native fish, Galaxiella pusilla . As G. pusilla can survive periods without surface water, this presents an opportunity for adaptive management, given G. holbrooki lack these adaptations. We develop a stochastic population model to explore the impact of G. holbrooki on G. pusilla and test the feasibility of both natural and management-induced drying to protect this species. Our results support recent empirical studies showing G. holbrooki are a serious threat to G. pusilla persistence, especially through impacts on larval survival. While persistence is more likely in water bodies that frequently dry out, even optimal natural drying regimes may be insufficient when impacts from G. holbrooki are high. However, management-induced drying may allow persistence of G. pusilla in sites inhabited by both species. Given our model outcomes, the biology of these species and the habitats they occupy, we recommend maintaining or restoring aquatic and riparian vegetation and natural drying regimes to protect G. pusilla from G. holbrooki, in addition to undertaking management-induced drying of invaded water bodies. Our results provide insights into how the effects of G. holbrooki may be mitigated for other native species, which is important given this species is perhaps the most pervasive invader of freshwater ecosystems. We conclude with a discussion of the potential for using disturbance processes in the management of invasive species more broadly in freshwater and terrestrial systems. Highlights: Invasive gambusia greatly increase risk of local extinction for dwarf galaxias. Extinction risk is reduced in invaded waterbodies that frequently dry out. Management-induced drying may protect dwarf galaxias facing severe gambusia impacts. Native species may have adaptations to disturbance that can be used when managing invasive species.